Esophageal tissue engineering : an in-depth review on scaffold design - Tan, J. Y. (2013)
Treatment of esophageal cancer often requires surgical procedures that involve removal. The current approaches to restore esophageal continuity however, are known to have limitations which may not result in full functional recovery. In theory, using a tissue engineered esophagus developed from the patient's own cells to replace the removed esophageal segment can be the ideal method of reconstruction. One of the key elements involved in the tissue engineering process is the scaffold which acts as a template for organization of cells and tissue development. While a number of scaffolds range from traditional non-biodegradable tubing to bioactive decellularized matrix have been proposed to engineer the esophagus in the past decade, results are still not yet favorable with many challenges relating to tissue quality need to be met improvements. The success of new esophageal tissue formation will ultimately depend on the success of the scaffold being able to meet the essential requirements specific to the esophageal tissue. Here, the design of the scaffold and its fabrication approaches are reviewed. In this paper, we review the current state of development in bioengineering the esophagus with particular emphasis on scaffold design.